1989
DOI: 10.1038/eye.1989.48
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new non-contact tonometer with Goldmann applanation

Abstract: with the Goldmann applanation tonometer is reported. Measurements of intra ocular pressure were obtained from 182 eyes of 94 patients. At low pressures «10 mmHg) the candidate tonometer tended to overestimate pressures obtained with the Goldmann tonometer whilst at high pressures (> 19 mmHg) those obtained by Goldmann applanation were underestimated. Between 10 and 19 mmHg there was no significant difference between readings obtained with either method. Up to 71 % of averaged Pulsair measurements fell within ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 9 publications
5
41
1
1
Order By: Relevance
“…Intraocular pressure has been positively correlated with body mass index (BMI) after adjusting for age, gender and BP (Mori et al 2000), and also with increasing degrees of myopia after adjusting for age, central corneal thickness (CCT) and other related factors (Nomura et al 2004). However, these previous studies carried out in Japan measured IOP using non-contact tonometry (NCT), which has relatively low accuracy and is more likely to be affected by CCT than is Goldmann applanation tonometry (GAT) (Moseley et al 1989;Rouhiainen & Terasvirta 1990;Mackie et al 1996;Recep et al 2001;Tonnu et al 2005). In one study, the mean IOP of participants obtained using NCT was reportedly 11.9 ± 2.5 mmHg and 11.5 ± 2.4 mmHg for male and female subjects, respectively (Nomura et al 1999), which was much lower than the mean of 14.5 ± 2.5 mmHg obtained from non-glaucoma participants in an epidemiological study carried out in Japan (Iwase et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure has been positively correlated with body mass index (BMI) after adjusting for age, gender and BP (Mori et al 2000), and also with increasing degrees of myopia after adjusting for age, central corneal thickness (CCT) and other related factors (Nomura et al 2004). However, these previous studies carried out in Japan measured IOP using non-contact tonometry (NCT), which has relatively low accuracy and is more likely to be affected by CCT than is Goldmann applanation tonometry (GAT) (Moseley et al 1989;Rouhiainen & Terasvirta 1990;Mackie et al 1996;Recep et al 2001;Tonnu et al 2005). In one study, the mean IOP of participants obtained using NCT was reportedly 11.9 ± 2.5 mmHg and 11.5 ± 2.4 mmHg for male and female subjects, respectively (Nomura et al 1999), which was much lower than the mean of 14.5 ± 2.5 mmHg obtained from non-glaucoma participants in an epidemiological study carried out in Japan (Iwase et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have also included eyes on anti-glaucoma medications. 1,3,8,10,13 The effect of treatment on the hydration properties of the cornea was overlooked as this was not the aim of the present study.…”
Section: 3-8mentioning
confidence: 99%
“…Past studies have showed that NCT overestimates IOP at lower values and underestimates at higher values when compared with GAT. [5][6][7][8] Tonnu et al were the only authors to show using the Canon model of NCT that NCT underestimated IOP at lower ranges and overestimated it at higher IOP ranges. 9 Our study showed a correction factor of 0.35mmHg for 10µm change in CCT for both GAT and NCT.…”
Section: 3-8mentioning
confidence: 99%
“…The oldest versions of this tonometer showed a fair agreement with GAT (±3 mmHg), but tended to overestimate the IOP for pressures lower than 10 mmHg and underestimate it for values above 19 mmHg. 50 However, modern non-contact tonometers correlate very well with GAT IOP, even though they tend to systematically overestimate it by between 0.12-0.58 mmHg. [51][52][53] With regard to the influence of corneal properties on noncontact tonometry measurements, it is likely that they are more influenced by CCT than GAT.…”
Section: Perkins Handheld Tonometer (Medtronic Solan Jacksonville Fmentioning
confidence: 99%
“…The benefits of non-contact tonometry include patient preference, less operator dependence, and no risk of infection transmission. [50][51][52][53] Pneumatonometer (Mentor, Model 30 Classic, Reichert, New York, USA) This is an easy-to-use instrument which provides fast and accurate tonometry readings. Utilizing a pneumatic pump, it can provide real time readings of IOP through a noninvasive applanation method.…”
Section: Perkins Handheld Tonometer (Medtronic Solan Jacksonville Fmentioning
confidence: 99%